Pemberian Kapsul Vitamin A pada Anak Usia 6-59 Bulan Berdasarkan Karakteristik Keluarga, Ibu dan Anak di Indonesia - Nur Choliza Azri; Demsa Simbolon (Politeknik Kesehatan Kemenkes Mamuju, 2022)
Vitamin A is an essential nutrient for humans. Need of Vitamin A must be met from the outside. The coverage of vitamin A capsule administration in Indonesia has not yet reached the national target and WHO recommendations. This study aims to determine the determinants of giving vitamin A capsules to children aged 6-59 months in Indonesia.The study used a cross sectional study design by conducting further analysis of the 2017 IDHS data. The research sample was 5,884 toddlers aged 6-59 months in Indonesia with the criteria for the last child born to women of childbearing age (WUS) aged 15-49 years. The independent variable was family characteristics. , mother and child. The dependent variable is the administration of vitamin A capsules to children under five. The results of the study found that 77.4% of Indonesian toddlers received vitamin A capsules according to the recommendations. Toddlers from families with very poor socioeconomic status have a risk of 1.085 times (OR 1.085; 95% CI 0.875-1.344), unaffordable health access has a risk of 1.224 times (OR 1.224; 95% CI 1.077-1.391), mothers who do not attend school have a risk of 1.625 times (OR 1.625: 95% CI 1.028-2.656) and infant of LBW have a risk of 2.519 times (OR 2.519; 95% CI 2.041-3.109) did not receive vitamin A. Toddlers from very low socioeconomic families, did not access health services, mothers with low education and those born with low birth weight are given priority in giving vitamin A capsules to prevent of deaseases caused by vitamin A deficiency.